Pengaruh Penambahan Buah Bit Merah terhadap Aktivitas Antioksidan, Sifat Fisik, dan Sensori Engay Food Berbasis Ikan Nila - Livia Isnaini; Nur rahman; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2023)
Engay food is a food whose texture is modified so that it produce a soft, smooth texture and is easy swallow texture. The main ingredient used is tilapia because it has an affordable price with the addition of beets to increase its nutritional value. This study aims to determine the effect of beetroot on the antioxidant, physical and sensory engay food of tilapia fish. The research method is beetroot flouring, tilapia grinding, shaping, and roasting. The result showed that the use of beetroot had an effect on antioxidant activity, physical and sensory properties of tilapia based engay food. The best treatment was on engay food products with the addition of 10% beetroot. The result of engay food has an antioxidant activity of 28,24%, has hue of 78,97 and chrome  of 15,3, beside that it also has cohesiveness 0,2175 J/m2, adhesion value 0,0575 mJ and a gumminess value of 164, 16 N/m2. The best engay for tilapia fish also contains water content of 68,70%, ash content of 1,04%, fat content of 1,89%, protein content of 9,80% and carbohydates by different 18,57%.